Image Processing of Motion for Security Applications - Duchon, Frantisek; Bučka, Peter; Szabová, Martina; Dekan, Martin; Beňo, Peter; Tolgyessy, Michal (European Scientific Journal, ESJ, 2017)
The aim of the article is a design, execution and examination of the computer vision systems, which processes digital video, reduces noise to a minimal level, and identifies a moving object together with estimation of its distance from the camera. For the image processing, library OpenCV was used. Two different methods were examined and implemented in control system. Some results are very similar in character and functionality with the use of security camera system, but the determining the distance of a given object is a new advanced ability of proposed system.